STEM TA’LIM TIZIMIDA FIZIKA FANINING O‘RNI - Kadirimbetova, G.R. (SCIENCE and SOCIETY, 2025)
The article analyzes the role and importance of physics in the STEM education system and modern approaches to its effective teaching. As an integral part of STEM, physics plays a key role in developing students’ scientific thinking, analytical reasoning, and problem-solving skills. The paper highlights the advantages of applying experiments, modeling, digital technologies, and engineering approaches in physics lessons.